Climate Change Mitigation and Adaptation Strategies for Sustainable Resource Management - Rusmayadi, Gusti; Nofirman, Nofirman; Fadhlihi, Andueriganta (Westscience Press, 2023)
The interplay between sustainable development and natural resource management has become central to addressing global challenges such as climate change, resource depletion, and social inequities. This study employs bibliometric analysis to explore the evolution, trends, and influences in this critical interdisciplinary field. Utilizing reputable databases, relevant publications are collected, preprocessed, and analyzed using VOSviewer. Co-authorship, citation, and keyword analyses unveil the intellectual landscape, prominent contributors, and core themes. Results showcase clusters such as climate change and resource management, highlighting challenges and strategies. Highly cited works underline key influences, from the natural-resource-based view of the firm to the triple bottom line concept. Insights empower researchers, policymakers, and practitioners to navigate the complexities of sustainable development and resource management.